Potential and Mechanisms for Stable C Storage in the Post-Mining Soils under Long-Term Study in Mitigation of Climate Change - Aneta Kowalska (MDPI AG, 2021)
Carbon storage in soil increases along with remediation of post-mining soils. Despite many studies on the issue of carbon sequestration in soils, there is a knowledge gap in the potential and mechanisms of C sequestration in post-mining areas. This research, including nuclear magnetic resonance analysis, determines the soil organic carbon formation progress in a long-term study of limestone (S1), and lignite (S2) post-mining soil under different remediation stages. The main remediation target is reforesting; however, S2 was previously amended with sewage sludge. The study showed that for S1, the O-alkyl groups were the dominant fraction in sequestered soil. However, for S2, increased fractions of acetyl-C and aromatic C groups within remediation progress were observed. The remediation of S1 resulted in improved hydrophobicity and humification; however, the decrease in aromatic groups’ formation and C/N ratio was noted. For S2, we noticed an increase for all indicators for sequestered C stability, which has been assigned to the used sewage sludge in remediation techniques. While both post-mining soils showed huge potential for C sequestration, S2 showed much higher properties of sequestered C indicating its higher stabilization which can suggest that soils non-amended with sewage sludge (S1) require more time for stable storage of C.